SINTESIS TiO2/Ti DENGAN TEKNIK ANODISASI DAN UJI AKTIVITAS FOTOKATALIS SEBAGAI ANTIBAKTERI Escherichia coli - Resti Fartiwi; Warsidah Warsidah; Anthoni Batahan Aritonang (Indonesian Journal of Pure and Applied Chemistry, 2019)
Titanium dioxide (TiO2) thin layer on the surface of metal Ti has been successfully synthesized using anodization method by varying the anodization times 30, 45 and 60 minutes. Characterization of TiO2/Ti with FTIR method gives absorption peaks at wave number 457,490 cm-1 and 796,635 cm-1, which is a Ti-O vibration. Visualization TiO2/Ti under SEM showed pores with diameter of 10-45 nm as an indication of the morphology of nanotubes, although the length of tubes have not been obtained. The results of XRD measurement give diffractogram at 2q: 25,337°; 37,891° and 48,074° and characterization DR-UV visible value 3,276 eV band gap which characterize crystalline anatase TiO2 phase. Photocatalytic TiO2/Ti exhibit antibacterial activity Escherichia coli were tested using the method of turbidimetry with a spectrophotometer at wavelength of 600 nm. Photocatalyst TiO2/Ti which are synthesized by anodizing process for 60 minutes have inhibitory bacterial growth better than synthesized for 30 minutes and 45 minutes.